A note on recent sightings of southern right whales (Eubalaena australis) along the east coast of Madagascar - Rosenbaum, Howard C. (J. Cetacean Res. Manage., 2020)
Southern right whales (Eubalaena australis) are distributed throughout the Southern Hemisphere, where they seasonally migrate between high latitude feeding grounds and low latitude breeding grounds. While there are detailed records of historical and recent whaling off the southern, southwestern and southeastern African coasts, historical catches in Madagascar’s waters are poorly documented. There have also been no recent, documented sightings of southern right whales off the east coast of Madagascar. Here we report two sightings, one of a single individual in Antongil Bay in northeastern Madagascar and the other of a mother and calf pair near Fort Dauphin on the southeastern coast. DNA obtained from a biopsy sample of the single animal showed it was a male possessing one of the common South Atlantic right whale mitochondrial haplotypes. The available DNA data provide limited suggestive evidence that the individuals documented off Madagascar represent long-distance migrants from the well-documented South African population. However, the possibility that these southern right whales are members of a small or remnant population from the historical whaling grounds of Delagoa Bay, Sofala Bay or the Crozet Island feeding grounds cannot be excluded. Regardless of population assignment for these individuals, it appears that some southern right whales may be using different parts of Madagascar’s east coast during the wintering season